PERENCANAAN PAKET WISATA BAHARI BERBASIS N.E.W.A (Nature. Eco. Wellness. Adventure) DI SULAWESI SELATAN - Machmud, Mukarramah; Amirullah; Aini, Windra; Wahim, Isdar; Djabbar, Atriana; Rinda, Ruth (Universitas Hasanuddin, 2023)
This research aims to identify the patterns of travel that have been created by the Travel Bureau in the tourist packages offered to tourists, map the potential for development of tourist travel pattern on the Spermonde Islands cluster in the Pangkajene Islands district and plan a model of marine tourism products in accordance with the N.E.W.A. approach. ( Nature. Eco.Wellness. Adventure).The research method qualitative research with a descriptive approach. The results of research show that South Sulawesi's most popular destinations in the tour package are Toraja, Tanjung Bira, rammang-rammang and Takabonerate.The sales value of such top destinations lies in the nature, adventure and culture aspects. From two days, one night, to eight days, seven nights. As well as tourist market share coming from outside South Sulawesi province. It requires more diverse and varied patterns of travel and sea tour packages with the NEWA concept.